LITERATURE REVIEW PENGARUH KEPERCAYAAN DAN KEPUASAN KONSUMEN/PELANGGAN PADA PROSES BISNIS E-COMMERCE (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine customer trust and satisfaction in E-commerce business processes. The research benefits to be obtained get an idea of customer trust and satisfaction in E-commerce business processes. This research uses a qualitative method with a literature review (SLR) study approach which aims to get a series of ideas about the factors that can affect the variables to be studied. The results of this study show that satisfaction has a significant effect on E-commerce business processes. and trust has a significant effect on E-commerce business processes.